Zinc as an Essential Nutritional Component of Human Body: A Systemic Review: Zinc as an Essential Nutritional Component of Human Body: A Systemic Review - Arabyaghoubi, Mostafa (International Journal of Pharmaceutical & Biological Archive, 2018)
Second to iron, zinc, which is widely distributed in the human body, is the most abundant element in human body. The human body has about 2–3 g of zinc, with the highest concentrations in the liver, pancreas, kidneys, bones, and muscles. Other tissues with a higher concentration of zinc include parts of the eye, prostate gland, spermatozoa, skin, hair, fingernail, and toenails. Searches were conducted by two independent researchers in international (PubMed, Web of science, Scopus, and Google scholar) and national (SID and Magiran) databases for related studies from the inception of the databases to September 2017 (without time limitation) in English and Persian languages. To ensure literature saturation, the reference lists of included studies or relevant reviews identified through the search were scanned. Absorption and excretion of zinc are carried out through hemostatic mechanisms that are not quite well known yet. The absorption mechanism consists of two paths. Albumin is the most important zinc plasma carrier. The amount transported in blood, in addition to zinc, depends on the availability of albumin. Zinc is a single intracellular ion with structural, catalytic, and regulatory roles. Zinc plays important structural roles as part of a multiprotein structure.